(untitled) (Research, Society and Development, 2020)
Introduction: At the end of 2019, a new coronavirus outbreak occurred in Wuhan. This new coronavirus, SARS-CoV-2, is the etiologic agent of COVID-19, a multisystemic inflammatory disease that can lead to serious lung damage. Due to the rapid spread of the disease, the pandemic was officially declared in March 2020 and the main preventive measures are the use of a mask, frequent hand hygiene, physical distance and cough etiquette. Objective: The objective of this work is to present an experience report of the curricular component “Biosafety in dental practice”, offered during the exceptional supplementary period. Methodology: This is a descriptive study, an experience report. Results: This component was offered between June and July 2020 at the Federal University of Rio Grande do Norte, campus Natal-RN, for 5 weeks, synchronously, with a workload of 45 hours, for a class of 40 students. The methodological and didactic resources developed were an expository class, a brainstorm, quiz, games, audiovisual material exhibition, seminars, readings and discussion of didactic texts and scientific articles, through platforms such as Sigaa / UFRN, Google meet, Kahoot, Mentimeter and Wondershare Filmora. In addition to teaching, there was the participation of a teaching intern (Postgraduate in Dental Sciences at UFRN) and two monitoring students (Graduate in Dentistry at UFRN). Conclusion: The remote format offered an educational ecosystem that provided temporary access, and which is a planned teaching modality with its own pedagogical proposal, materials, environment and format.